Guru Pendidikan Agama Kisten Sebagai Teladan Nilai Karakter Kristiani (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
This study explores the role of Christian religious education teachers in shaping students’ character within the school setting. Employing a literature review method, the research analyzes secondary sources that discuss character formation theories grounded in Biblical principles and Christian education approaches. Key values examined include love, honesty, responsibility, forgiveness, and compassion, which are integrated into the learning process. The findings reveal that Christian religious education teachers hold a crucial position as educators, mentors, and role models, responsible for guiding students in internalizing these values. Character development is fostered not only through formal lessons but also through teachers’ personal example, the incorporation of Biblical teachings into classroom activities, and the encouragement of practical faith expressions in daily life. This holistic approach ensures that students not only understand Christian moral principles cognitively but also embody them in behavior and interactions with others. The study emphasizes that effective character formation relies on consistent modeling of values by teachers, meaningful integration of religious teachings into pedagogy, and opportunities for students to practice faith-based actions, thereby strengthening both moral awareness and ethical conduct.